Tocilizumab As A Potential Treatment for SARS-CoV2 Pneumonia in Cancer Patients: A Case Report of A Patient with Clinical-Radiological Dissociated Response - Moreno, Irene; Miguel, Maro de; Álvarez, Rafael; Cubillo, Antonio; Calvo, Emiliano (Archives of Clinical and Medical Case Reports, 2020)
In December 2019, a novel virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused an outbreak of pneumonia in China. As known, this infection then resulted in a pandemia, being still some territories accross the World suffering from that. Currently, there is no specific treatment or approved vaccine and many clinical trials are investigating potential drugs. Among them, immunomodulators seems a group of drugs that could be useful in the Coronavirus-19 disease (Covid-19). Specially, in those cases where a cytokine storm occurs. This involves a considerable release of proinflammatory cytokine including several interleukins and tumour necrosis factor α (TNF-α) . Here, we report the successful treatment of a metastatic colorectal cancer patient hospitalized due to SARS-CoV-2 pneumonia with tocilizumab, an humanized monoclonal antibody against the interleukin-6 receptor (IL-6R).